Historical policy of communist Romania in the opinions of PPR diplomacy - Nowak, Krzysztof (Balcanica Posnaniensia. Acta et studia, 2024)
The article proposes to look at the phenomenon of the historical politics of the authorities of communist Romania through the prism of opinions on this subject from the diplomacy, also communist, of the Polish People's Republic. It is about opinions of representatives of a state whose citizens during the communist period were not subjected to and did not succumb to such strong political indoctrination as in other satellite states of the Kremlin on the subject of a state which, from the 1960s onwards, conducted the most independent and distanced foreign politics from the Kremlin among these satellites and which went furthest among these states in instrumentally using historical politics and the often accompanying nationalism for political purposes. As the Polish observers have argued, the Romanian authorities saw in the image of Romanians and Romanian history created by them a valuable tool to shape for themselves the favor of society, its views and public sentiment depending on the political demand of the moment. It was most controversial among Poles, but supported by the Romanian public, that the Romanian authorities used history to more or less openly attack the Soviet Union in the name of defending their sovereignty. The Polish authorities also viewed with distance the theory deriving modern Romanians from the ancient Dacians and generally considered Romanian historiography to be biased and unreliable. In spite of the fall of communism, unlike in Poland, the picture of Romanian history shaped earlier, with a strong nationalist accent, is still readily accepted by Romanians.